Human Monkeypox: A Comprehensive Overview of Epidemiology, Pathogenesis, Diagnosis, Treatment, and Prevention Strategies. - Martínez-Fernández, Diana Emilia; Fernández-Quezada, David; Casillas-Muñoz, Fidel Antonio Guadalupe; Carrillo-Ballesteros, Francisco Josué; Ortega-Prieto, Ana María; Jiménez-Guardeño, José Manuel; Regla-Nava, Jose Ángel (My University, 2023)
Monkeypox virus (MPXV) is an emerging zoonotic virus that belongs to the Orthopoxvirus genus and presents clinical symptoms similar to those of smallpox, such as fever and vesicular-pustular skin lesions. However, the differential diagnosis between smallpox and monkeypox is that smallpox does not cause lymphadenopathy but monkeypox generates swelling in the lymph nodes. Since the eradication of smallpox, MPXV has been identified as the most common Orthopoxvirus to cause human disease. Despite MPXV being endemic to certain regions of Africa, the current MPXV outbreak, which began in early 2022, has spread to numerous countries worldwide, raising global concern. As of the end of May 2023, over 87,545 cases and 141 deaths have been reported, with most cases identified in non-endemic countries, primarily due to human-to-human transmission. To better understand this emerging threat, this review presents an overview of key aspects of MPXV infection, including its animal reservoirs, modes of transmission, animal models, epidemiology, clinical and immunological features, diagnosis, treatments, vaccines, and prevention strategies. The material presented here provides a comprehensive understanding of MPXV as a disease, while emphasizing the significance and unique characteristics of the 2022 outbreak. This offers valuable information that can inform future research and aid in the development of effective interventions.
Keywords: Viruela de los monos humana - Epidemiología; Viruela de los monos humana - Patogénesis; Viruela de los monos humana - Prevención; Zoonosis; Monkeypox; Poxvirus; Virus; Virology; Pathogenesis